THE POTENTIAL OF WINE TOURISM: AN EXPLORATORY STUDY OF NEW ZEALAND - DAVID A. COHEN (Centre For Tourism Planning and Development, 2008)
Recent published information suggests that New Zealand's wine industry continues to grow rapidly. An activity related to the wine industry, wine tourism, is developing in wineries that provide cellar door sales, tasting rooms, restaurants, tours to their vineyards, and even accommodation. These developments demonstrate the potential of wine tourism as an alternative activity for travellers to rural areas, and as a business concept for wineries. However, still today research on wine tourism in New Zealand has been limited, including the way in which winery visitors are presented in the wine tourism literature. This paper reports the results of an exploratory study that investigated potential relationships between different winery visitor groups in New Zealand, including their commercial contribution in the form of winery expenditures. The results confirm significant differences among various visitor groups when comparing their age, income, or whether they are domestic or international. These findings could have significant implications for the wine and wine tourism industries.